The impact of board structure and ownership structure on firm performance: An evidence from blue chip firms listed in Indonesian stock exchange - Basyith, A.; Fauzi, Fitriya; Idris, M. (Virtus interpress, 2015)
This study attempts to investigate the impact of board structure and ownership structure on firm performance of blue chip firms listed in Indonesia Stock Exchange. Blue chip firms is referred as LQ45 in Indonesian Stock Exchange, and it consists of 45 the most liquid firms among other firm listed in Indonesian Stock Exchange. Using balanced panel of 45 blue chip firms which spans from 2010 to 2014; this study employs a logistic regression. The findings reveal that apart from independent commissioner and audit committee, all variables have a significant impact on firm performance.